Digital image analysis of skin neoplasms evaluated by lectin histochemistry: potential marker to biochemical alterations and tumour differential diagnosis Análise digital de imagens de neoplasias da pele avaliadas pela histoquímica com lectinas: marcador potencial para alterações bioquímicas e diagnóstico diferencial de tumores - Mario R. Melo-Júnior; Jorge Luiz S. Araújo-Filho; Vasco José Ramos M. Patu; Marcos Cezar F. de Paula Machado; Eduardo I.C. Beltrão; Luiz B. Carvalho Jr (Sociedade Brasileira de Patologia Clínica, 2006)
The present study aims to evaluate, through lectin histochemistry, the alterations in the expression of cell surface carbohydrate between benign and malignant lesions of skin using computer image analysis. Skin fragments were obtained through biopsies and diagnosed as basal cell carcinoma (BCC), epidermoid carcinoma (EpC), trichoepithelioma (TE), keratoacanthoma (KA), seborrheic keratosis (SK) and actinic keratosis (AK). Lectins Con A, WGA, PNA, UEA-I and LTA were used in histochemistry study. Image analysis was carried out in a workstation using OPTIMAS TM software system. PNA strong binding pattern to studied tumours evidenced the high expression of D-galactose residues in the epidermal neoplasms when compared to other sugars recognized by the other lectins. Among benign neoplasms, KA presented a high expression of glucose/mannose, alpha-fucose and D-galactose residues evidenced by the intense staining of Con A (94.7%), LTA (84.2%) and PNA (89.4%), respectively. Malignant tumours showed distinct binding patterns. EpC presented significant binding only by PNA lectin. BCC was differentially stained in comparison to the staining pattern observed in benign lesions such as TE. Qualitative (lectin histochemistry) and quantitative (digital image analysis) data obtained in this study evidenced those lectins are potential markers to biochemical alterations in skin neoplasms. O presente estudo objetivou avaliar, através da histoquímica com lectinas, as alterações na expressão dos carboidratos da superfície celular entre lesões benignas e malignas da pele usando análise de imagens computadorizadas. Fragmentos de pele foram obtidos através de biópsias e diagnosticados como carcinoma basocelular (CBC), carcinoma epidermóide (EpC), tricoepitelioma (TE), cerato acantoma (KA), ceratose seborreica (CS) e ceratose actínica (CA). As lectinas Con A, WGA, PNA, UEA-I e LTA foram usadas no estudo histoquímico. A análise de imagens foi realizada numa estação de análise usando o sistema OPTIMAS TM de análises. A PNA tem sido largamente utilizada no estudo de tumores, evidenciando a expressão de D-galactose nas neoplasias epidérmicas; esse açúcar apresenta alta expressão quando comparado com os outros reconhecidos pelas demais lectinas. Entre as neoplasias benignas, KA apresentou alta expressão glucose/manose; resíduos de alfa-fucose e D-galactose apresentaram intensa marcação com ConA (94,7%) LTA (84,2%) e PNA (89,4%), respectivamente. Os tumores malignos mostraram marcações distintas: EpC apresentou marcação significativa somente com a lectina PNA; CBC apresentou diferente padrão de marcação quando comparado ao observado nas lesões benignas assim como no TE. Os resultados qualitativos (análise de imagens) e quantitativos (histoquímica com lectinas) desse estudo evidenciaram que as lectinas têm grande potencial como marcadores de alterações bioquímicas nas neoplasias da pele.